Mechanical characterisation of woven kenaf fabric as reinforcement for composite materials - Dhar Malingam, Sivakumar; Ng, Lin Feng; Kamarolzaman, Anita Akmar; Hong, Tzy Yi; Ab Ghani, Ahmad Fuad (Taylor and Francis Inc., 2021)
Kenaf is one of the common economic crops favoured by many plantations due to its many uses. The fabric is produced from the bast fibres of kenaf plant which is biodegradable and tough. This research aims at investigating the effect of fabric orientation, moisture content and different batches (storage age) of kenaf fabrics on the tensile properties. The tensile properties of kenaf fabrics in two different directions which are warp and weft are compared. Furthermore, two different batches of plain-woven kenaf fabric were analysed to study their tensile properties. In the case of moisture content effect, the fabrics in warp and weft orientations were tested at saturated moisture condition for their tensile properties. The findings concluded that the tensile strength of kenaf fabric in the weft was 28.3 % and 24.7% higher than warp orientation for the old and new batches of kenaf fabrics respectively. In overall, moisture uptake of kenaf fabrics reduced the tensile strength of kenaf fabrics regardless of different fabric orientations and batches. The results also demonstrated that the different batches of kenaf fabrics had no significant effect on the tensile properties.